The personal librarian [large type] - Benedict, Marie; Murray, Victoria Christopher (Random House Large Print, 2021)
Hired by J.P. Morgan to curate a collection of rare manuscripts, books, and artwork for his newly built Pierpont Morgan Library, Belle da Costa Greene becomes one of the most powerful women in New York despite the dangerous secret she keeps.